Burst activity and ultrafast activation kinetics of CaV1.3 Ca2+ channels support presynaptic activity in adult gerbil hair cell ribbon synapses. (21st June 2013) - Zampini, Valeria; Johnson, Stuart L.; Franz, Christoph; Knipper, Marlies; Holley, Matthew C.; Magistretti, Jacopo; Masetto, Sergio; Marcotti, Walter
Key points:   The transfer of sound information to the brain relies on the precise release of neurotransmitter from sensory inner hair cell (IHC) ribbon synapses.   Neurotransmitter release from IHCs is triggered by Ca 2+ entry mainly through one type of Ca 2+ channel (CaV 1.3).   In this study we show that in near‐physiological conditions Ca 2+ channels open very rapidly following a stimulus with a delay of about 50 μs.   Despite the open probability of the Ca 2+ channels being very low, they can switch to a burst‐like mode during a stimulus, maximizing Ca 2+ influx into IHCs.   These results help us to better understand how IHCs are able to accomplish high‐fidelity signal transfer at individual auditory ribbon synapses. Abstract  Auditory information transfer to afferent neurons relies on precise triggering of neurotransmitter release at the inner hair cell (IHC) ribbon synapses by Ca 2+ entry through CaV 1.3 Ca 2+ channels. Despite the crucial role of CaV 1.3 Ca 2+ channels in governing synaptic vesicle fusion, their elementary properties in adult mammals remain unknown. Using near‐physiological recording conditions we investigated Ca 2+ channel activity in adult gerbil IHCs. We found that Ca 2+ channels are partially active at the IHC resting membrane potential (−60 mV). At −20 mV, the large majority (>70%) of Ca 2+ channel first openings occurred with an estimated delay of about 50 μs in physiological conditions, with a mean open time of 0.5 ms. Similar to other ribbon synapses, Ca 2+ channels in IHCs showed a low mean open probability (0.21 at −20 mV), but this increased significantly (up to 0.91) when Ca 2+ channel activity switched to a bursting modality. We propose that IHC Ca 2+ channels are sufficiently rapid to transmit fast signals of sound onset and support phase‐locking. Short‐latency Ca 2+ channel opening coupled to multivesicular release would ensure precise and reliable signal transmission at the IHC ribbon synapse.